"A Foundation for Something Bigger": Community College Students' Experience of Remediation in the Context of a Learning Community. (July 2014) - Schnee, Emily
This longitudinal, qualitative study explores developmental English students' experience of remediation in the context of a first-semester learning community (LC). Conducted at an urban community college in the Northeast, data were collected through semi-structured interviews conducted over a 3-year period with a cohort of 15 students who were placed into a first-semester LC that linked the lowest level of developmental English with Introduction to Psychology and a student development course. Findings shed light on students' changing perceptions of their placement in remedial English, their insights into LC participation, and reveal implications for community college research and practice. Developmental students' experiences, voices, and perspectives are the focus of this study and are analyzed in the context of the highly contentious debate over college remediation.